2018
DOI: 10.1097/j.pain.0000000000001373
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of spinal 15-LOX-1 attenuates TLR4-dependent, nonsteroidal anti-inflammatory drug–unresponsive hyperalgesia in male rats

Abstract: Although nonsteroidal anti-inflammatory drugs are the first line of therapeutics for the treatment of mild to moderate somatic pain, they are not generally considered to be effective for neuropathic pain. In the current study, direct activation of spinal Toll-like 4 receptors (TLR4) by the intrathecal (IT) administration of KDO2 lipid A (KLA), the active component of lipopolysaccharide, elicits a robust tactile allodynia that is unresponsive to cyclooxygenase inhibition, despite elevated expression of cyclooxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 84 publications
(150 reference statements)
3
18
0
Order By: Relevance
“…Tactile allodynia: Tactile allodynia was evaluated using manual von Frey filaments with buckling forces between 0.02 and 2 g (Touch Test, Stoelting Co.) applied to the mid-plantar surface of each hind paw using the up-down method as previously described (Chaplan et al, 1994;Gregus et al, 2018). Mice were acclimated to the testing room in a 4-sided acrylic chamber with only one transparent wall (3 x 3 x 7.5 in) and placed on a metal mesh grid under controlled lighting conditions (~100 lux) for a minimum of 60 min (baseline measurements) or 15 min (experimental timepoints).…”
Section: Evaluation Of Spinal Lps-induced Pain-like Behaviors In Scrn...mentioning
confidence: 99%
“…Tactile allodynia: Tactile allodynia was evaluated using manual von Frey filaments with buckling forces between 0.02 and 2 g (Touch Test, Stoelting Co.) applied to the mid-plantar surface of each hind paw using the up-down method as previously described (Chaplan et al, 1994;Gregus et al, 2018). Mice were acclimated to the testing room in a 4-sided acrylic chamber with only one transparent wall (3 x 3 x 7.5 in) and placed on a metal mesh grid under controlled lighting conditions (~100 lux) for a minimum of 60 min (baseline measurements) or 15 min (experimental timepoints).…”
Section: Evaluation Of Spinal Lps-induced Pain-like Behaviors In Scrn...mentioning
confidence: 99%
“…Pretreatment with TLR4 antagonist (TAK-242) had no effect on the initial hypersensitivity, but the late paralgesia can be prevented [ 80 ]. It was found that TLR4-induced production of the bioactive lipids by 12/15-lipoxygenase (12/15-LO) partially mediates neural sensitization, although the contribution of 12/15-LO expressed in other cell types cannot be excluded [ 81 ]. In conclusion, these studies indicated that TLR mediates RA pain through direct or indirect mechanism.…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%
“…LOX enzymes can also metabolize linoleic acid (LA) into 9-or 13hydroxyoctadecadienoic acid which have demonstrated some bioactivity [32]. In addition, inhibiting 15-LOX has demonstrated anti-hyperalgesic effects in an intrathecal LPS pain model and prevented formalin flinching and tactile allodynia [33].…”
Section: Lipoxygenase Metabolitesmentioning
confidence: 99%